A core outcome set for future endometriosis research: an international consensus development study. (30th March 2020) - Duffy, JMN; Hirsch, M; Vercoe, M; Abbott, J; Barker, C; Collura, B; Drake, R; Evers, JLH; Hickey, M; Horne, AW; Hull, ML; Kolekar, S; et al.
Abstract : Objective: To develop a core outcome set for endometriosis. Design: Consensus development study. Setting: International. Population: One hundred and sixteen healthcare professionals, 31 researchers and 206 patient representatives. Methods: Modified Delphi method and modified nominal group technique. Results: The final core outcome set includes three core outcomes for trials evaluating potential treatments for pain and other symptoms associated with endometriosis: overall pain; improvement in the most troublesome symptom; and quality of life. In addition, eight core outcomes for trials evaluating potential treatments for infertility associated with endometriosis were identified: viable intrauterine pregnancy confirmed by ultrasound; pregnancy loss, including ectopic pregnancy, miscarriage, stillbirth and termination of pregnancy; live birth; time to pregnancy leading to live birth; gestational age at delivery; birthweight; neonatal mortality; and major congenital abnormalities. Two core outcomes applicable to all trials were also identified: adverse events and patient satisfaction with treatment. Conclusions: Using robust consensus science methods, healthcare professionals, researchers and women with endometriosis have developed a core outcome set to standardise outcome selection, collection and reporting across future randomised controlled trials and systematic reviews evaluating potential treatments for endometriosis. Tweetable abstract: @coreoutcomes for future #endometriosis research have been developed @jamesmnduffy. Tweetable abstract: @coreoutcomes for future #endometriosis research have been developed @jamesmnduffy. This paper includes Author Insights, a video abstract available at https://vimeo.com/rcog/authorinsights16157